2010
DOI: 10.1158/1535-7163.mct-10-0309
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of DNA Methyltransferase and Histone Deacetylase Inhibitors Induce DNA Damage in Small Cell Lung Cancer Cells: Correlation of Resistance with IFN-Stimulated Gene Expression

Abstract: Because epigenetic inhibitors can reduce cancer cell proliferation, we tested the hypothesis that concurrent inhibition of histone acetylation and DNA methylation could synergistically reduce the viability of small cell lung cancer (SCLC) cells. Sub-IC 50 concentrations of the DNA methyltransferase (DNMT) inhibitor decitabine (5-AZA-dC) and the histone deacetylase (HDAC) inhibitors (LBH589 or MGCD0103) synergistically reduced the proliferation of five of nine SCLC cell lines. Loss of viability of sensitive SCL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…In contrast, recent studies suggest that IFNs and other inflammatory cytokines may augment tumor progression (de Visser et al, 2006;Calogero et al, 2007;DeNardo and Coussens, 2007;Bektas et al, 2008;DeNardo et al, 2008). ISG signatures that may be predictive of DNA damage resistance in bronchial and breast carcinomas have been described (Einav et al, 2005;Weichselbaum et al, 2008;Luszcek et al, 2010). Supporting the potential pro-tumor activity of some ISGs, we and others identified G1P3 (ISG 6-16, IFI6), a gene robustly stimulated by IFNs, as an antiapoptotic protein (Tahara et al, 2005;Cheriyath et al, 2007).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, recent studies suggest that IFNs and other inflammatory cytokines may augment tumor progression (de Visser et al, 2006;Calogero et al, 2007;DeNardo and Coussens, 2007;Bektas et al, 2008;DeNardo et al, 2008). ISG signatures that may be predictive of DNA damage resistance in bronchial and breast carcinomas have been described (Einav et al, 2005;Weichselbaum et al, 2008;Luszcek et al, 2010). Supporting the potential pro-tumor activity of some ISGs, we and others identified G1P3 (ISG 6-16, IFI6), a gene robustly stimulated by IFNs, as an antiapoptotic protein (Tahara et al, 2005;Cheriyath et al, 2007).…”
Section: Introductionsupporting
confidence: 52%
“…Contrary to evidence for IFNs as suppressive factors in cancer evolution, recent studies suggested that some of its target genes (ISGs) may contribute to the progression of malignancies (Tahara et al, 2005;Cheriyath et al, 2007;Bektas et al, 2008;Weichselbaum et al, 2008;Luszcek et al, 2010). However, the functional consequence of upregulated ISGs in cancer development and progression has not been well delineated (Sorbello et al, 2003;Bektas et al, 2008;Weichselbaum et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…A combination of bromodeoxyuridine and distamycin A induced cellular senescence, activation of STAT1, and upregulation of ISGs (32). Luszczek and colleagues used a combination of DNA-methyltransferase I and histone deacetylase (HDAC) inhibitors (HDACi) to induce DNA damage in small cell lung cancer cell lines and found that resistant cell lines overexpressed STAT1 and ISGs (33). These results suggest that STAT1 overexpression is associated with resistance of tumor cells to antitumor drugs.…”
Section: Chemoresistance and The Stat1 Pathwaymentioning
confidence: 99%
“…32,33 Importantly, synergistic effects of HDACi and the DNMT inhibitor DAC were reported for growth inhibition, DNA damage, and apoptosis induction in different tumor entities. [34][35][36] Again, the underlying mechanism of action is not validated yet, but HDACi appear to decelerate removal of incorporated DAC from DNA, thereby enhancing the harmful action of DAC. 37 In the setting of the 2 major types of esophageal cancer, this study addressed the basic molecular effects (e.g.…”
Section: Introductionmentioning
confidence: 99%